2020
DOI: 10.3390/jcm9123929
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Viability of Free Flaps after Extracorporeal Perfusion Using a Modified Hydroxyethyl Starch Solution

Abstract: Background: In free flap surgery, tissue is stored under hypothermic ischemia. Extracorporeal perfusion (EP) has the potential to extend storage time and the tissue’s perspective of survival. In the present study, the aim is to improve a recently established, simplified extracorporeal perfusion system. Methods: Porcine musculus rectus abdominis were stored under different conditions. One group was perfused continuously with a simplified one-way perfusion system for six hours, while the other received only a si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…16 Using a modified heart-lung machine, Slater et al were able to provide ECP to porcine myocutaneous rectus abdominis flaps for 24 hours with no signs of necrosis using oxygenated histidine-tryptophan-ketoglutarate. [17][18][19] Fichter et al reported promising results in humans, demonstrating the feasibility and safety of short-term ECP (►Fig. 1) for up to 4 hours to salvage eight human critically perfused and congested-free radial forearm flaps.…”
Section: Vascularized Composite Allotransplantation Free Flapsmentioning
confidence: 99%
“…16 Using a modified heart-lung machine, Slater et al were able to provide ECP to porcine myocutaneous rectus abdominis flaps for 24 hours with no signs of necrosis using oxygenated histidine-tryptophan-ketoglutarate. [17][18][19] Fichter et al reported promising results in humans, demonstrating the feasibility and safety of short-term ECP (►Fig. 1) for up to 4 hours to salvage eight human critically perfused and congested-free radial forearm flaps.…”
Section: Vascularized Composite Allotransplantation Free Flapsmentioning
confidence: 99%
“…For mid-thermic and subnormothermic conditions, perfusion without an oxygen carrier has been attempted by Pendexter ( 34 ), Veraza ( 37 ), and Kruit ( 42 ) in limb models and by Taeger et al in multiple studies ( 65 , 67 , 69 ) ( Tables 1 , 2 ). Most of these studies do not include SCS controls except for that of Kruit et al in which they report worse outcomes after 18 h of perfusion in histology vs. SCS controls yet preserved muscle contractility after replantation.…”
Section: Perfusatementioning
confidence: 99%
“…Taeger et al ( 65 , 67 , 68 ), in their multiple studies, reported a wide range of weight gain (49.5%–99%) after 6 h of perfusion in swine rectus abdomins flaps. They reported better tissue preservation with perfusion.…”
Section: Weight Gain and When To Stop Perfusionmentioning
confidence: 99%